Harnessing the Intrinsic Reactivity within the Aplysinopsin Series for the Synthesis of Intricate Dimers: Natural from Start to Finish - Skiredj, Adam; Beniddir, Mehdi A.; Joseph, Delphine; Bernadat, Guillaume; Evanno, Laurent; Poupon, Erwan (Synthesis, 2015)
Aplysinopsin monomers are considered as plausible biosynthetic precursors of the wider aplysinopsin family of marine alkaloids. The idea of harnessing their intrinsic reactivity to undertake the synthesis of dictazoles or cycloaplysinopsins logically emerged from this status. These biosynthetic considerations led us to the first total syntheses of dictazole B and other valuable cyclobutanes. When further exploiting pre-encoded reactivity, our first total synthesis of tubastrindole B originated from the ring-expansion cascade of its dictazole-type precursor. Moreover, the isolation of a transient biosynthetic intermediate combined with dimerization outcomes of a hydantoin-containing monomer allowed us to explain the formation of cycloaplysinopsins A and B.1 Introduction2 Easy Access to Dictazole Cyclobutanes3 Synthesis of Cycloaplysinopsins by Ring Expansion4 Conclusion and Future Prospects
Keywords: alkaloids; aplysinopsins; biomimetic synthesis; total synthesis; natural products